1951
DOI: 10.6028/jres.047.017
|View full text |Cite
|
Sign up to set email alerts
|

First dissociation constant of phosphoric acid from 0-degrees-C to 60-degrees-C; Limitations of the electromotive force method for moderately strong acids

Abstract: An accurate det.ermination by t he electro motive-force m ethod of t he di ssoc iat ion constant of an acid as strong as t he first ac idi c g roup of phospho ric acid r eq uires t hat the hydrogen-ion concen t rat ion be estab li s hed wi t h greater accuracy than is usually attainable. The un cer tain quantity is t he activ ity coe ffi cie nt of hydrochloric acid in the particular mixture und e r st ud y. It is shown th at the calculation of this coefficient by t he DebyeHi.ickel eq uat ion , which afford s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1965
1965
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…As pKI=2.148 in ordinary water [36], IlpK = 0.214, 0.125, or 0.234, depending on which of these assumptions about the activity coefficient terms is chosen.…”
Section: Results Of Present Workmentioning
confidence: 99%
“…As pKI=2.148 in ordinary water [36], IlpK = 0.214, 0.125, or 0.234, depending on which of these assumptions about the activity coefficient terms is chosen.…”
Section: Results Of Present Workmentioning
confidence: 99%
“…It has been reported that phosphate ions form ion pairs with Ca 2+ as shown in the reactions (11) and (12), 29 where phosphate ions are involved in the equilibrium reactions (8) to (10). 30,31 When HPO 2− 4 was excluded from r-SBF (p-r-SBF), the actual Ca 2+ concentration in the fluid increased. The increased Ca 2+ concentration accelerates the nucleation rate of calcite by increasing the ionic activity product of the fluid for calcite.…”
Section: Discussionmentioning
confidence: 99%
“…Derivative r-SBFs excluding either HCO The −log (IP) for hydroxyapatite 24 and calcite 30 are 117.0 and 8.6, respectively. Superscript a, b, and c indicate supersaturation, saturation and undersaturation, respectively, with respect to the corresponding phases.…”
Section: Preparation Of the Sbfsmentioning
confidence: 99%
“…A and B were set to 0.5242 and 0.3318, respectively [Bates, 1964], Values used for a, were 9 for IP , 6 for Ca2' and 4 for P 0 43" [Kielland, 1937]. The dissociation constants employed for phosphoric acid were 6.22 • 10 ' [Bates, 1951], 6.58 ■ 10 s Aeree, 1945 and6.61 • 10 13 [Bjcrrum andUnmack, 1929]. The degree of saturation was expressed as the difference between the logarithms o f the ion product and the solubility product constant for hydroxyapatite.…”
Section: Calculationsmentioning
confidence: 99%